2013
DOI: 10.1177/000348941312201107
|View full text |Cite
|
Sign up to set email alerts
|

Association between Tinnitus and Sleep Disorders in the General Japanese Population

Abstract: Insomnia and other sleep disorders were significantly associated with tinnitus in Japanese adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 25 publications
(42 reference statements)
3
60
0
Order By: Relevance
“…Nevertheless, not all patients affected by tinnitus develop insomnia. In a Japanese population‐based cohort study of community adults, it was found that over 78% of the patients with tinnitus were not affected by insomnia . A retrospective sleep study of inpatients with insomnia and tinnitus, but without sleep apnea, periodic leg movements, or a severe psychiatric disorder, showed no differences in sustained attention tasks, subjective daytime tiredness, and depression rating scores when compared with age‐ and sex‐matched inpatients with primary insomnia but not tinnitus .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, not all patients affected by tinnitus develop insomnia. In a Japanese population‐based cohort study of community adults, it was found that over 78% of the patients with tinnitus were not affected by insomnia . A retrospective sleep study of inpatients with insomnia and tinnitus, but without sleep apnea, periodic leg movements, or a severe psychiatric disorder, showed no differences in sustained attention tasks, subjective daytime tiredness, and depression rating scores when compared with age‐ and sex‐matched inpatients with primary insomnia but not tinnitus .…”
Section: Introductionmentioning
confidence: 99%
“…Difficulty in initiating and maintaining sleep and poor perceived quality of sleep were significantly associated with tinnitus. 9 A Nigerian study on 183 community elderly subjects with tinnitus also found that difficulty with falling asleep and early morning wakefulness were significant symptoms of their insomnia. 10 Nevertheless, not all patients affected by tinnitus develop insomnia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, anxiety and depression severity have been correlated with tinnitus severity, and tinnitus prevalence may even decrease within a cohort as depression symptoms improve . Tinnitus is furthermore associated with sleep disorders, including insomnia, and can cause difficulty in initiating and maintaining sleep, and lead to poor overall quality of sleep . These patients often suffer from greater distress and difficulty with concentration, irritability, and loss of control …”
Section: Introductionmentioning
confidence: 99%
“…15 Tinnitus is furthermore associated with sleep disorders, including insomnia, and can cause difficulty in initiating and maintaining sleep, and lead to poor overall quality of sleep. 16 These patients often suffer from greater distress and difficulty with concentration, irritability, and loss of control. 17 In contrast, Shargorodsky et al, in their study of the National Health and Nutrition Examination Survey data, failed to find a significant association between frequent tinnitus and major depression.…”
Section: Introductionmentioning
confidence: 99%